The Effect of Corporate Social Responsibility (CSR) Disclosure on Tax Avoidance with Gender as Moderating Variable in Mining Companies - Luxmawati, Friska; Prihantini, Febrina Nafasati (Universitas Semarang, 2020)
This study aims to determine the effect of Corporate Social Responsibility (CSR) disclosure on tax avoidance in Indonesia and also to determine the relationship between Corporate Social Responsibility (CSR) disclosure on tax avoidance with gender as the moderating variable. This study was conducted in 19 mining companies listed on the Indonesia Stock Exchange (IDX) during the 2016-2017 period using secondary data. Samples were selected using purposive sampling method with the total of 38 observations. Data analysis in this study uses simple regression analysis and Moderated Regression Analysis (MRA) with independent variable of Corporate Social Responsibility (CSR), dependent variable of tax avoidance, and moderating variable of gender. The results showed that Corporate Social Responsibility (CSR) had no effect on tax avoidance. Gender is able to moderate the effect of Corporate Social Responsibility (CSR) on tax avoidance